The Heart of Business - Joly, Hubert (Ascent Audio, 2021)
How to unleash "human magic" and achieve improbable results. Hubert Joly, former CEO of Best Buy and orchestrator of the retailer's spectacular turnaround, unveils his personal playbook for achieving extraordinary results. Joly and his team rebuilt the company into one of the nation's favorite employers, vastly increased customer satisfaction, and dramatically grew Best Buy's stock price, while making Best Buy a leader in sustainability and innovation. In The Heart of Business, Joly shares the philosophy behind the resurgence of Best Buy: pursue a noble purpose, put people at the center of the business, create an environment where every employee can blossom, and treat profit as an outcome, not the goal. Putting this approach into practice requires radically rethinking how we view work, how we define companies, how we motivate, and how we lead. Joly shares memorable stories, lessons, and practical advice, all drawn from his own personal transformation from a hard-charging McKinsey consultant to a leader who believes in human magic. The Heart of Business is a timely guide for leaders ready to abandon old paradigms and reinvent capitalism so that it contributes to a sustainable future. Visit TheHeartofBusiness.org to learn more
Online resource; Title from title page (viewed May 4, 2021)
Keywords: Livres numériques; Audiobooks